Playing the Man in the Book of Ruth: Reshaping the Masculine Ideal - Purcell, Richard (Biblical interpretation, 2022)
Many scholars have productively analyzed the book of Ruth to explore gender roles and norms. Few studies, though, have brought masculinity theory to bear on the book of Ruth, and those that have primarily focus on the character of Boaz. However, other characters ‘play the man’ in this narrative, notably Ruth herself. Though Boaz is labeled as an אישׁ גבור חיל, Ruth often better performs the masculine ideal represented by this label. She enters dangerous situations to protect and provide for Naomi. Moreover, Ruth initiates and manipulates sexual contact in order to produce progeny. The narrative presents the characters of Ruth, Boaz, and, at times, Yhwh performing masculine roles with varying levels of success. This essay contends that the book takes up previously assumed norms of masculinity and reshapes them in light of a changing socio-political context.